PERBEDAAN PENGETAHUAN DAN PERILAKU KONSUMSI SAYUR BUAH SETELAH PEMBERIAN EDUKASI GIZI DENGAN VIDEO ANIMASI DAN LEAFLET PADA ANAK SD - Fajar Salekah (Poltekkes Kemenkes Semarang, 2022)
Background: Lack of knowledge can affect the behavior of consumption of vegetables and fruit in children. One of the ways to increase knowledge and behavior in consuming vegetables and fruit is by providing education, in educating researchers using animated videos and leaflets.Subject : The purpose of this study was to analyze differences in knowledge and behavior of fruit vegetable consumption by using video animation and leaflet methods in elementary school children in the Cibinong area.Methods: This type of research is a quasi-experimental research design with a controlled group pre-post design. Analysis of the data in this study using the Paired Sample T-test, Independent T-test and the Mann-Whitney test.Results: The results showed that there was a difference in knowledge before and after being given an intervention in the form of nutrition education with the animated video method (p = 0.000, = 29) and leaflets (p = 0.034, = 9). There was a significant difference in the consumption behavior of vegetables and fruit before and after the nutrition education intervention using animated videos (p = 0.000, = 27) and leaflets (p = 0.037, = 5).Conclusions: Based on the results of these data, it is concluded that animated videos are more effective for teaching and learning compared to leaflets.